Raising the bar 3: Essential finance and accounting function staff skills, training needs and challenges in driving productivity - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2014)
Tight manpower environment is likely to continue to be a feature of the Singapore economy. Thus, productivitygrowth is key, for firms to cope with tight labour market and sustaining higher wages.1 Beyond Singapore,productivity is also an area of focus for other Asian economies like Hong Kong and Japan, who face similarchallenges, such as rapidly ageing populations and shrinking workforces.